Pengaruh Label Pasupati pada Produk Dupa terhadap Minat Beli Konsumen - Kusuma Dewi, Made Ika (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2020)
Balinese religious ceremonies are an integration of sublime values that have evolved from one tradition to the next. Cultural rituals will require the objects used to carry out the ritual process. These objects that can be used as a business opportunity in every religious ceremony such as the items needed are incense, flowers, and Canang. the emergence of incense labeled Pasupati with many benefits produce many diverse variations in incense products and can be said that the incense labeled this pasupati can compete in market competition.The results of the research is that without the innovation and innovative of the entrepreneurs (distributors) will not be the incense labeled this post. The significance of the label of the Pasupati in the incense products include economic distributors want to benefit as much and for incense only give positive energy instead of giving atman or spirit to the incense. There is a significant influence on incense labeled this pasupati in the intention of buying consumers. The advice of researchers is expected to add insight to incense labeled Pasupati and as a reference in religious sciences.